End-tidal carbon dioxide (ETCO2) at intubation and its increase after 10 minutes resuscitation predicts survival with good neurological outcome in out-of-hospital cardiac arrest patients. (December 2022) - Baldi, Enrico; Caputo, Maria Luce; Klersy, Catherine; Benvenuti, Claudio; Contri, Enrico; Palo, Alessandra; Primi, Roberto; Cresta, Ruggero; Compagnoni, Sara; Cianella, Roberto; Burkart, Roman; De Ferrari, Gaetano Maria; et al.
Abstract: Aim: To evaluate whether end-tidal carbon dioxide (ETCO2) value at intubation and its early increase (10 min) after intubation predict both the survival to hospital admission and the survival at hospital discharge, including good neurological outcome (CPC 1–2), in patients with out-of-hospital cardiac arrest (OHCA). Methods: All consecutive OHCA patients of any etiology between 2015 and 2018 in Pavia Province (Italy) and Ticino Region (Switzerland) were considered. Patients died before ambulance arrival, with a "do-not-resuscitate" order, without ETCO2 value or with incomplete data were excluded. Results: The study population consisted of 668 patients. An ETCO2 value at intubation > 20 mmHg and its increase 10 min after intubation were independent predictors (after correction for known predictors of OHCA outcome) of survival to hospital admission and survival at hospital discharge. Relative to hospital discharge with good neurological outcome, ETCO2 at intubation and its 10-min change were confirmed predictors both individually and in a bivariable analysis (OR 1.83, 95 %CI 1.02–3.3; p = 0.04 and OR 3.9, 95 %CI 1.97–7.74; p < 0.001, respectively). This was confirmed also when accounting for gender, age, etiology and location. After further adjustment for bystander and CPR status, presenting rhythm and EMS arrival time, the ETCO2 change remained an independent predictor. Conclusions: ETCO2 value > 20 mmHg at intubation and its increase during resuscitation improve the prediction of survival at hospital discharge with good neurological outcome of OHCA patients. ETCO2 increase during resuscitation is a more powerful predictor than ETCO2 at intubation. A larger prospective study to confirm this finding appears warranted.